Blockchain Applications in Network Engineering: From Secure Routing to Decentralized Identity Management - Ranjbar, Obaidullah; Aziz Rastagari, Mohammad; Azimi, Sanayee; Danish, Jawad (Journal of Advanced Computer Knowledge and Algorithms, 2025)
Blockchain technology has emerged as a promising solution to address critical security and privacy challenges in network engineering. Its decentralized, immutable, and transparent nature enables enhanced secure routing and decentralized identity management, which are vital for modern network infrastructures such as IoT, smart cities, and vehicular networks. This study systematically reviews recent literature from reputable databases, including IEEE Xplore, ScienceDirect, MDPI, ACM Digital Library, and Web of Science, covering publications from 2016 to 2024. Using a structured search and selection process, 29 relevant studies were analyzed to explore the effectiveness of blockchain-based secure routing mechanisms, features of decentralized identity frameworks, and the technical challenges related to blockchain integration. The findings reveal that blockchain significantly improves network security by preventing threats like route hijacking and Sybil attacks while empowering users with self-sovereign identity control. However, challenges such as energy consumption, latency, scalability, and interoperability remain critical obstacles. The review recommends further development of energy-efficient consensus algorithms, scalable architectures, and interoperability standards to enable broader adoption. Overall, blockchain presents a transformative approach for securing and managing complex network environments, provided that its limitations are carefully addressed in future research.